The Analysis of the Effect of a Chayotte Extract on the Radiolabeling of Blood Elements in Diabetic Rats - Dire, G.F.; Vasconcelos, S.D.D.; Siqueira, P.R.A.; Duarte, R.M.; Almeida, M.C.L.; Rodrigues, J.S.; Oliveira, J.C.S.; Fernandes, M.L.; Bernardo-Filho , M. (Pakistan Journal of Nutrition, 2006)
The use of natural products occurs around the world. The labeling of blood constituents with technetium-99m (99m Tc) has been influenced by natural extracts and oxidative stress. Some studies suggested that maternal diabetes can affect the embryology environmental and this fact could help to elucidate that the oxidative stress may be related to the disturb of the gene expression which is essential in the control of the ontogenetic processes. We evaluated the influence of a chayotte ( Sechium edule ) extract on the labeling of blood elements with 99m Tc in diabetic female rats. The animals were treated with chayotte during 7 days and samples of blood were withdrawn. The samples were incubated with stannous chloride and with 99mTc. Plasma(P) and blood cells (BC) were isolated, also precipitated with trichloroacetic acid and soluble (SF) and insoluble fractions (IF) separated. The radioactivity (ATI%) was rated in RBC, IF-P and IF-C in a well counter. In the diabetic group it was observed an increase in the radioactivity in BC (from 43.65 ± 1.83 to 59.47 ± 1.83 and in the IF-BC (from 26.22 ± 23.58 to 73.28 ± 23.58). It was noticed that the referred extract has normalizing the efficiency of radiolabeling in the diabetic animals which have received the referred extract. The effect of chayotte extract probably, could be explained by the metabolization of the chayotte that would be capable of inducing the generation of active metabolites with oxidant properties probably altering the activity of cell membrane.